Effects of Oral Stanozolol Used in the Prevention of Postoperative Deep Vein Thrombosis on Fibrinolytic Activity - Sue-Ling, H M; Davies, J A; Prentice, C R M; Verheijen, J H; Kluft, C (Thrombosis and Haemostasis, 1985)
Plasminogen, fibrinogen, antithrombin III, euglobulin lysis time, tissue plasminogen activator (t-PA) and fast-acting t-PA inhibitor were measured in 21 patients receiving either stanozolol (10 mg orally given for 14 days preoperatively) or subcutaneous heparin, during a continuing comparative trial in the prevention of postoperative deep vein thrombosis.Stanozolol treatment resulted in significant (p <0.01) increases between the 14th and 1st preoperative days in the plasma concentrations of plasminogen (3.4 to 4.9 Cu/ml) and antithrombin III (107% to 132%); t-PA levels did not increase significantly (6.0 to 16.0 mU/ml; p >0.1). There were significant (p <0.02) falls in fast-acting t-PA inhibitor (132% to 75%) and fibrinogen (2.4 to 1.8 g/1).Surgery reversed the changes in fibrinolytic activity seen preoperatively in the stanozolol-treated patients, and similar changes were seen in the heparin-treated group. In this dosage, stanozolol does not appear to prevent the fibrinolytic shutdown which occurs after elective major surgery.
Keywords: Stanozolol; Fibrinolytic activity; Deep vein thrombosis